Growth and characterization of C-13 enriched 4H-SiC for fundamental materials studies - Jang, Yeon-Suk; Sakwe, Aloysius; Wellmann, Peter; Juillaguet, Sandrine; Peyre, Herve; Camassel, J.; Steeds, J. W. (Materials Science Forum, 2007)
We have carried out the growth and basic characterization of isotopically enriched 4H-(SiC)-C-13 crystals. in recent years the growth of 13 C enriched 6H-SiC has been performed in order to carry out fundamental materials studies (e.g. determination of phonon energies, fundamental bandgap shift, carbon interstitial defect study, analysis of the physical vapor transport (PVT) growth process). For electronic device applications, however, the 4H-SiC polytype is the favored material, because it offers greater electron mobility. In this paper we present the growth of 4H-(SiC)-C-13 single crystals with up to 60% of C-13 concentration. From a physical point of view we present first results on phonons as well as the fundamental bandgap energy shift due to 13C incorporation into the SiC lattice.
Keywords: (SiC)-C-13